The Neanderthal in the karst: First dating, morphometric, and paleogenetic data on the fossil skeleton from Altamura (Italy). Issue 82 (May 2015) - Lari, Martina; Di Vincenzo, Fabio; Borsato, Andrea; Ghirotto, Silvia; Micheli, Mario; Balsamo, Carlotta; Collina, Carmine; De Bellis, Gianluca; Frisia, Silvia; Giacobini, Giacomo; Gigli, Elena; Hellstrom, John C.; et al.
Abstract: In 1993, a fossil hominin skeleton was discovered in the karst caves of Lamalunga, near Altamura, in southern Italy. Despite the fact that this specimen represents one of the most extraordinary hominin specimens ever found in Europe, for the last two decades our knowledge of it has been based purely on the documented on-site observations. Recently, the retrieval from the cave of a fragment of bone (part of the right scapula) allowed the first dating of the individual, the quantitative analysis of a diagnostic morphological feature, and a preliminary paleogenetic characterization of this hominin skeleton from Altamura. Overall, the results concur in indicating that it belongs to the hypodigm of Homo neanderthalensis, with some phenetic peculiarities that appear consistent with a chronology ranging from 172 ± 15 ka to 130.1 ± 1.9 ka. Thus, the skeleton from Altamura represents the most ancient Neanderthal from which endogenous DNA has ever been extracted.